TINJAUAN HUKUM ISLAM DAN HUKUM POSITIF TERHADAP PENETAPAN DISPENSASI NIKAH: Studi di Pengadilan Agama Kelas 1A Palu - Mauliyana, Sri; Sapruddin; Wahyuni; Nurinayah (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2023)
This thesis focuses on how judges consider the class 1A religious court in Palu in determining the marriage dispensation and an analysis of Islamic and positive law regarding marriage dispensations in the Palu Class 1A Religious Court. This research uses qualitative research based on empirical law collected through interview studies, documentation studies, observation and data reduction, data presentation, verification and checking the validity of the data. The results of this research show that the judge's consideration in granting marriage dispensation looks at the legal facts, that there are indeed witnesses in the application for marriage dispensation. The judge will consider the application for marriage dispensation that has been submitted by the applicant based on the existing evidence. Looking at the benefits, the Panel of Judges in determining a case must have a legal basis for the case they are handling and grant the request if it is very urgent. Then, Islam does not regulate the age limit for marriage, the age limit for a person to marry only mentions signs of female maturity and men having wet dreams. The judge basically uses various considerations and legal bases, namely Law Number 1 of 1974, Compilation of Islamic Law (KHI), as well as fiqhiyah rules. However, the panel of judges prioritized the concept of maslahah because it was to prevent undesirable things. The principle is that the prospective bride and groom must mature their body and soul in order to realize the goal of marriage well without ending in divorce and to have good and healthy offspring. Therefore, underage marriages must be prevented, with this provision the age limit for marriage is set in the Marriage Law. rigid. This means that it does not provide an opportunity for anyone to do it.